Pengembangan Strategi Bersaing untuk Meningkatkan Kualitas Sekolah Menengah Pertama - Setiyanti, Dwi; Dwikurnaningsih, Yari (Universitas Kristen Satya Wacana, 2023)
The background of this study is the decreasing number of students and classes in one junior high school. This study aims to determine the strengths, weaknesses, opportunities, and threats in the school by developing suitable competitive strategies to improve the school quality and the number of students and classes. This research is qualitative research using the research and development (R & D) method with the Borg and Gall development model which is limited to the seventh step. The study was conducted in a junior high school. The subjects of the study were school principal, teachers, staff, and school observers. Data was collected by interview, documentation studies, questionnaires, and Focus Group Discussion (FGD) techniques. Data was analyzed with a qualitative descriptive analysis using Miles and Huberman model. Activities in data analysis included data reduction, data display, and conclusion drawing/verification. The result of the study show that the school is in quadrant II which indicates that the condition of the school is quite stable, but it faces many obstacles, therefore it is necessary to carry out a diversification strategy. The proposed diversification strategy includes curriculum diversification and service expansion and continuous improvement efforts.